2003
DOI: 10.1177/070674370304800306
|View full text |Cite
|
Sign up to set email alerts
|

Are Mental Health Services for Children Distributed According to Needs?

Abstract: Objectives: The purpose of this study was twofold: 1) to determine whether publicly funded mental health services and resources available in 4 large regions in the province of Quebec were distributed according to the mental health needs of children aged 6 to 14 years and 2) to assess whether the variations in mental health services and resources across the 4 regions had changed over a 5-year period. Methods: Indicators of need according to the child's parent (presence of mental disorder, measure of adaptation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…Papers from LMICs included several from Thailand [ 12 , 27 , 28 ], Mexico [ 29 ], Chile [ 30 ] and Brazil [ 8 , 31 ]. Studies from high-income countries tended to focus on access to specialised services and procedures such as mental health services [ 22 , 23 ], and procedures for circulatory disease [ 22 , 25 ]. They also focused on distinct populations such as children [ 23 ], the elderly [ 24 ] and psychiatric patients [ 22 ] rather than the population as a whole.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Papers from LMICs included several from Thailand [ 12 , 27 , 28 ], Mexico [ 29 ], Chile [ 30 ] and Brazil [ 8 , 31 ]. Studies from high-income countries tended to focus on access to specialised services and procedures such as mental health services [ 22 , 23 ], and procedures for circulatory disease [ 22 , 25 ]. They also focused on distinct populations such as children [ 23 ], the elderly [ 24 ] and psychiatric patients [ 22 ] rather than the population as a whole.…”
Section: Resultsmentioning
confidence: 99%
“…Studies from high-income countries tended to focus on access to specialised services and procedures such as mental health services [ 22 , 23 ], and procedures for circulatory disease [ 22 , 25 ]. They also focused on distinct populations such as children [ 23 ], the elderly [ 24 ] and psychiatric patients [ 22 ] rather than the population as a whole. Two studies showed that despite systems of free universal coverage, there was greater inequity, measured in terms of waiting times and receipt of procedures, for interventions which were non-urgent or elective, or for which there was a lack of clearly defined treatment protocols [ 21 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Based on the literature on mental health service use, we included the predictors of child sex (Bussing et al 2003;Sourander et al 2008;Zimmerman 2005), psychological adjustment (McMiller and Weisz 1996), parents' perceived impact of child illness , single parent status (Briggs-Gowan et al 2000), parents' emotional adjustment (Verhulst and Van der Ende 1997), and their history of mental health service use (Wu et al 1999(Wu et al , 2001. We also considered the availability of mental health services within the community, which has been recognized as relevant to service planning and delivery (Bai et al 2009;Blais et al 2003), but has not been included in previous studies of help-seeking. Third, we examined what happened at each agency that parents contacted.…”
Section: The Current Studymentioning
confidence: 99%
“…Multiple aspects of treating children with mental health problems require improvement, including overcoming barriers to care and increasing service use (Blais, Breton, Fournier, St.-Georges, & Berthiaume, 2003;McKay, McCadam, & Gonzales, 1996). Recent estimates, based on a combination of epidemiological studies indicate that of the 14% of children with mental health disorders, only 18% of children receive specialized services for their difficulties (Waddell, Offord, Shepherd, Hua, & McEwan, 2002).…”
mentioning
confidence: 99%